Bonding Sans Bondage: Feminist Perspective of Taslima Nasrin’s Lajja (International Journal of Food and Nutritional Sciences, 2022)
Indian mythology, religion and society have always held women in high esteem. Due to the working of narrow-minded and selfish interests of forces tempered by male power, women have lost their place in the outer world and in their own family where they are assigned restricted duties. The silenced women always tend to show their mettle whenever socio-political situations warrant. This paper seeks to highlight how Taslima Nasrin in her novel Lajja describes women are sexually harassed, abducted and subjected to varied kinds of physical and mental torture that may result even in their deaths. The insecure condition of women and the change of identity in order to escape from the rioters have been described openly in Nasrin’s novel.